Immunohistochemistry Screening of Different Tyrosine Kinase Receptors in Canine Solid Tumors—Part I: Proposal of a Receptor Panel to Predict Therapies - Dos Anjos, Denner Santos [UNESP]; Civa, Patrick Antônio Sonaglio; Werner, Juliana; Vicente, Igor Simões Tiagua; Fonseca-Alves, Carlos Eduardo [UNESP] (MDPI, 2024)
The use of tyrosine kinase inhibitors (TKI) has been growing in veterinary oncology and in the past few years several TKI have been tested in dogs. However, different from human medicine, we lack strategies to select patients to be treated with each TKI. Therefore, this study aimed to screen different tumor subtypes regarding TKI target immunoexpression as a predictor strategy to personalize the canine cancer treatment. It included 18 prostatic carcinomas, 36 soft tissue sarcomas, 20 mammary gland tumors, 6 urothelial bladder carcinomas, and 7 tumors from the endocrine system. A total of 87 patients with paraffin blocks were used to perform immunohistochemistry (IHC) of human epidermal growth factor receptor 2 (HER-2), epidermal growth factor receptors 1 (EGFR1), vascular endothelial growth factor receptor 2 (VEGFR-2), platelet derived growth factor receptor beta (PDGFR-β), c-KIT, and extracellular signal-regulated kinase 1/2 (ERK1/ERK2). The immunohistochemical screening revealed a heterogeneous protein expression among histological types with mesenchymal tumors showing the lowest expression level and carcinomas the highest expression. We have demonstrated by IHC screening that HER2, EGFR1, VEGFR-2, PDGFR-β and ERK1/ERK2 are commonly overexpressed in dogs with different carcinomas, and KIT expression is considered relatively low in the analyzed samples.
Keywords: dogs; epidermal growth factor; immunohistochemistry; platelet-derived growth factor receptor; receptor tyrosine kinase; target therapy; vascular endothelial growth factor